Social Acceptance Among Children with Learning Difficulties - Ainin, Ima Kurrotun; Tabrin, Nita Nitiya Intan (ASANKA : Journal of Social Science and Education, 2024)
This study explores social acceptance among children with general learning difficulties/children with special needs (CSN) using a qualitative approach involving structured interviews with 144 students and in-depth interviews with three teachers. The research highlights the social dynamics of CSN inclusion, emphasizing the importance of a supportive environment, positive teacher attitudes, and peer education programs in promoting social integration. Findings show that students, particularly females at the junior high level, generally hold positive attitudes towards CSN. At the same time, concerns over emotional behaviors like tantrums create interaction challenges, especially among elementary school boys. Teachers ensure equal participation for CSN through individualized support, inclusive activities, and peer support systems. This study's originality lies in its comprehensive exploration of peer attitudes across educational levels. It offers insights into gender differences, behavioral challenges, and the teacher's role in promoting inclusive education through adaptive teaching methods and social support.